ANALISIS BUDAYA POPULER DALAM GERAKAN PRODEMOKRASI DI THAILAND PADA TAHUN 2020 - Kahanjak Mahar, Rachel Koinonia Agape; Erawan, Ni Luh Putra; Puspitasari, Ni Wayan Radita Novi (Jurnal Nawala Politika; Vol 2 No 1 (2023): Jurnal Ilmu Politik, 2023)
This research examines how the use of symbols and signs of popular culture in the prodemocracy movement in Thailand in 2020 is aimed at mobilizing the public and influencing the narratives of contemporary political movements. Through building theories on mass culture and democratic participation, this study reveals that popular culture facilitates the emergence of contemporary movements through the adoption of the three finger salute from The Hunger Games and the slogan "He Who Must Not Be Named" from Harry Potter used by the pro- democracy so that it places how social movements adhere to popular culture in drawing the artistic framework of making state repression read into perceived injustice, and how civil participation in the public space is transformed as a demand against the Thai government.